Influence of Cold-TRP Receptors on Cold-Influenced Behaviour - Dibesh Thapa; Brentton Barrett; Fulye Argunhan; Susan D. Brain (MDPI AG, 2021)
The transient receptor potential (TRP) channels, TRPA1 and TRPM8, are thermo-receptors that detect cold and cool temperatures and play pivotal roles in mediating the cold-induced vascular response. In this study, we investigated the role of TRPA1 and TRPM8 in the thermoregulatory behavioural responses to environmental cold exposure by measuring core body temperature and locomotor activity using a telemetry device that was surgically implanted in mice. The core body temperature of mice that were cooled at 4 °C over 3 h was increased and this was accompanied by an increase in UCP-1 and TRPM8 level as detected by Western blot. We then established an effective route, by which the TRP antagonists could be administered orally with palatable food. This avoids the physical restraint of mice, which is crucial as that could influence the behavioural results. Using selective pharmacological antagonists A967079 and AMTB for TRPA1 and TRPM8 receptors, respectively, we show that TRPM8, but not TRPA1, plays a direct role in thermoregulation response to whole body cold exposure in the mouse. Additionally, we provide evidence of increased TRPM8 levels after cold exposure which could be a protective response to increase core body temperature to counter cold.